STUDY ON PREDICTION DEFLECTION AT GIRDER MIDSPAN OF LARGE TONNAGE RIGID CONNECTION LEGS GANTRY CRANE BASED ON ENERGY METHOD - ZHANG DaPeng; CHENG WenMing; CAI Kun (Jixie qiangdu)
It is the most important inspection index the deflection value of the gantry crane girder under rated load in the overall test.For large tonnage gantry crane in the overall test,prepared the experimental weight is often very difficult at the site,or even impossible perform test.In the text,it is deduced the girder deflection curve equation under the considering effects of the leg bending moment to the girder deflection When the concentrated load is applied to the position of the girder midspan.The girder deflection values can be obtained under three-small-loads at the girder midspan,and the coefficients of gantry frame girder flexural equation can be obtained.In this way,the deflection of the large tonnage gantry crane is predicted through the data of the three-small-loads method in the test.The three-small-loads method provides a practical and effective method for the prediction of the girder deflection of large tonnage gantry structure.